Lifestyles and diet related to nutritional status and the risk of DM2 in young women from two Colombian universities: Estilos de vida y alimentación relacionados con el estado nutricional y el riesgo de DM2 en mujeres jóvenes de dos universidades colombianas - Rodríguez Leyton, Mylene (2023)
Objective: To analyze the lifestyles and diet related to nutritional status and the risk of DM2 and in female students of two Colombian universities.Methods: a descriptive, cross-sectional, multidimensional and exploratory study, carried out in a sample of 220 women, NyD students selected by random medsampling of proportions[1]. A questionnaire was applied to identify sociodemographic variables, lifestyles related to food and DM2 risk according to the FINDRISC test; BMI, waist circumference, fat percentage, and active body substance index (IAKS) were determined. Bivariate analysis was performed using Statgraphics v.16, the chi2 test was applied with 95% confidence and statistical significance (p <0.05).Results: Overweight and obesity according to BMI (21.4%) showed statistical significance with the frequency of consumption of sugary drinks, packaged products, sugars and sweets, fast foods and alcoholic beverages; These two eating practices were related to very high cardiovascular risk by waist circumference and excessive fat percentage, which also presented significance with excessive screen time; the IAKS was related to the classification of physical activity. According to the FINDRISC test, 91% had DM2 risk factors; 20.5% presented medium risk and 2.3% high.Conclusions: Lifestyle and diet were related to anthropometric indicators: body weight, fat distribution, and body composition; are risk factors for the development of DM2 in young women. It is necessary to promote protective factors to maintain a healthy weight.